Can Self-Regulation Work? Lessons from the Private Security and Military Industry - Richemond-Barak, Daphné (2014)
The private security and military industry has undergone a dramatic shift over the past decade—from an under-regulated sphere of activity to one in which an array of self-regulatory schemes has emerged. These regulatory initiatives took shape as states, security companies, and the broader public recognized the need to clarify the legal framework applicable to private security and military companies. Private contractors, once regarded as mercenaries, have over the past two decades played an increasingly central role in support of modern militaries. Reasons for this phenomenon range from budgetary policy to the need for specialized expertise most readily available in the private sector. Given the prominence of private contractors on the modern battlefield, a consensus has formed around the need to establish standards to govern the conduct of this increasingly prominent category of non-state actor. The industry’s expanding scope of activity and client base — composed of not only states, but also international organizations, non-governmental organizations, and multinational corporations operating in volatile environments — has made regulation an even stronger priority. In just a few years, working jointly with states and civil society, the private security and military industry has developed a sophisticated self-regulatory framework applicable to its activities